2012
DOI: 10.1128/aem.06586-11
|View full text |Cite
|
Sign up to set email alerts
|

Key Residues for Controlling Enantioselectivity of Halohydrin Dehalogenase from Arthrobacter sp. Strain AD2, Revealed by Structure-Guided Directed Evolution

Abstract: bHalohydrin dehalogenase from Agrobacterium radiobacter AD1 (HheC) is a valuable tool in the preparation of R enantiomers of epoxides and ␤-substituted alcohols. In contrast, the halohydrin dehalogenase from Arthrobacter sp. AD2 (HheA) shows a low S enantioselectivity toward most aromatic substrates. Here, three amino acids (V136, L141, and N178) located in the two neighboring active-site loops of HheA were proposed to be the key residues for controlling enantioselectivity. They were subjected to saturation mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 27 publications
0
29
0
1
Order By: Relevance
“…Strikingly, in HheA the aromatic side chain of the Senantiomer of the substrate was docked in the pocket formed by residues Leu141, Asn144, and Asn178, among which Leu141 and Asn178 are at the equivalent positions of Trp139 and Asn176 in HheC. By manipulating these active-site residues, a variant with an inverted enantioselectivity (from E S of 21.7 to E R of 13) and an S-selective HheA variant toward 2-CPE have been developed (Asn178Ala) (26). The results indicated that the two enzymes might share similar mechanisms for controlling enantioselectivity.…”
Section: Guo Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Strikingly, in HheA the aromatic side chain of the Senantiomer of the substrate was docked in the pocket formed by residues Leu141, Asn144, and Asn178, among which Leu141 and Asn178 are at the equivalent positions of Trp139 and Asn176 in HheC. By manipulating these active-site residues, a variant with an inverted enantioselectivity (from E S of 21.7 to E R of 13) and an S-selective HheA variant toward 2-CPE have been developed (Asn178Ala) (26). The results indicated that the two enzymes might share similar mechanisms for controlling enantioselectivity.…”
Section: Guo Et Almentioning
confidence: 99%
“…Kinetic parameters of the wildtype HheC and its variants toward 1,3-DCP and both enantiomers of 2-CPE were taken in 50 mM Tris-SO 4 buffer (pH 8.0) at 37°C by monitoring halide liberation using purified enzymes as described before (26,34).…”
Section: Materials Rac-2-mentioning
confidence: 99%
See 1 more Smart Citation
“…Some general examples of stereoselective syntheses of halohydrins, as precursors of optically active cyclic ethers, are (a) the reduction of halogen-substituted ketones by means of hydrides complexed with chiral ligands (e.g., CBS-catalyst) [20,21]; (b) stereoselective hydrogenation processes run in the presence of Rh/Ru catalysts [22][23][24]; (c) microbial [25][26][27][28] or isolated enzymes-mediated [29] stereoselective reductions of α-halo-acetophenones; and (d) the kinetic resolution of racemic mixtures using dehalogenases (e.g., HheC from Agrobacterium radiobacter AD1) [30,31]. Our group recently focused on the development of new bio-catalyzed whole-cell biotransformations for the enantioselective preparation of chiral secondary alcohols, which are valuable precursor compounds for active pharmaceutic ingredients (APIs) [32][33][34][35].…”
Section: Screening Of Biocatalysts For the Stereoselective Reduction mentioning
confidence: 99%
“…For this purpose, a viable approach employs rational and random protein engineering strategies that can yield drastically improved and functionally diverse enzyme variants (28). Such strategies have been successfully applied to HheA2 (29)(30)(31) and HheC (13,(32)(33)(34), addressing specific drawbacks of the respective parental enzymes and yielding HHDH mutants with sometimes substantial improvements with regard to target reactions. Nevertheless, parental sequences will always govern the overall accessible sequence space in every protein engineering study.…”
mentioning
confidence: 99%